Impact of statin treatment on non-invasive tests based predictions of fibrosis in a referral pathway for NAFLD - Juan G Abraldes; Mang Ma; Mustafa Al-Karaghouli; Sonia Fuentes; Tracy Davyduke (BMJ Open Gastroenterology)
Objective In non-alcoholic fatty liver disease (NAFLD), fibrosis determines the risk of liver complications. Non-invasive tests (NITs) such as FIB-4, NAFLD Fibrosis Score (NFS) and Hepamet, have been proposed as a tool to triage NAFLD patients in primary care (PC). These NITs include AST±ALT in their calculations. Many patients with NAFLD take statins, which can affect AST/ALT, but it is unknown if statin affects NITs fibrosis prediction.Methods We included 856 patients referred through a standardised pathway from PC with a final diagnosis of NAFLD. 832 had reliable vibration controlled transient elastography (VCTE) measurements. We assessed the effects of statins on the association between NITs and VCTE at different fibrosis thresholds.Results 129 out of 832 patients were taking a statin and 138 additional patients had indication for a statin. For any given FIB-4 value, patients on a statin had higher probabilities of high VCTE than patients not on a statin. Adjusting for body mass index, diabetes and age almost completely abrogated these differences, suggesting that these were related to patient’s profile rather to a specific effect of statins. Negative predictive values (NPVs) of FIB-4 <1.3 for VCTE >8, 10, 12 and 16 were, respectively, 89, 94, 96% and 100% in patients on a statin and 92, 95, 98% and 99% in patients not on a statin. Statins had similar impact on Hepamet predictions but did not modify NFS predictions.Conclusion In patients with NAFLD referred from PC, those on statins had higher chances of a high VCTE for a given FIB-4 value, but this had a negligible impact on the NPV of the commonly used FIB-4 threshold (<1.3).